Studi Eksperimental Pengaruh Kemiringan Sudut Terhadap Alat Destilasi Air Laut Memanfaatkan Energi Matahari - C A Siregar; Ahmad Marabdi Siregar (Rekayasa Material, Manufaktur dan Energi, 2019)
Indonesia is one country that is in a tropical climate that promises sunshine of all time. The abundant potential of solar radiation can be utilized in a distillation device to convert sea water into fresh water. This research aims to build a distillation device as a provider of clean water. Test equipment is designed and built with black fiber material with a size of 1.25 m x 0.8 m with a 3 mm thick glass cover with a capacity of 3600 ml of sea water. To find out the effectiveness of the distillation apparatus, it was tested with three variations of slope angles namely 300, 400, and 500. Tests carried out in the city of Medan. The testing method is done by evaporating seawater, evaporation occurs because of the absorption of heat from the sun through a solar collector's plate. The result obtained an effective slope angle is 300 with a production of 650 ml of fresh water. In addition to fresh water production, it is also known that the maximum sea water temperature is 730C at 12:20 WIB, the radiation heat transfer rate is 92.86 Watt